Kontribusi Kecerdasan Buatan dalam Mewujudkan Pemahaman Nilai Pancasila di Era Modern - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Sinta Nirmala; Ahmad Natsir Fairus Ilyas; Laila Nur Kusuma; Anastya Salsabila Putri (Desentralisasi : Jurnal Hukum, Kebijakan Publik, dan Pemerintahan, 2025)
The use of Artificial Intelligence (AI) has now become one of the crucial aspects in the advancement of information technology throughout the world. This article aims to connect the values ​​of Pancasila as the moral basis of the Indonesian nation with the ethics of using artificial intelligence and its impact on the country. As the philosophical foundation of the state, Pancasila contains deep ethical values ​​and can be used as guidelines in the application of AI that are in line with the moral and ethical principles that apply in Indonesia. Pancasila education has an important role as an ethical framework in the context of the development and application of AI. In this article, we will discuss the application of Pancasila values ​​in technological developments so that they remain in line with the nation's identity, as well as explore the various positive and negative impacts that may arise from the use of AI. Furthermore, this study seeks solutions that can be implemented by the government, companies, and society to overcome these negative impacts. Using a descriptive qualitative approach, this study aims to explore and understand in depth the relationship between Pancasila values ​​and ethics in the use of AI, especially in the context of the development of information technology in Indonesia. This approach is very appropriate for examining social phenomena, values, and meanings contained in policies or implementation of technology in society.